Postveraison Shoot Trimming Reduces Cluster Compactness without Compromising Fruit Quality Attributes in Organically Grown Sangiovese Grapevines - Bondada, Bhaskar; Ignacio Covarrubias, Jose; Tessarin, Paola; Boliani, Aparecida Conceicao [UNESP]; Marodin, Gilmar; Rombola, Adamo Domenico (Amer Soc Enology Viticulture, 2016)
Vine performance following preveraison shoot trimming is well documented, but the consequences of this treatment later in the season are poorly understood. Here, a four-year study was conducted in a mature vineyard of Sangiovese (clone 12T) grafted onto Kober 5BB rootstock at a spacing of 1 m x 2.8 m (intra-and interrow) to analyze the influence of postveraison shoot trimming on vine growth characteristics, cluster architecture (cluster compactness), and yield from a physiological viewpoint. The treatments consisted of shoot trimming during postveraison in a randomized block design with eight replications (six vines each). Three treatments were imposed when soluble solids reached 15 Brix in August (40 to 45 days before expected harvest): light trimming (14 nodes), severe trimming (10 nodes), and an untrimmed control. Following the treatments, vine growth characteristics, cluster morphology, and fruit quality attributes were measured. Postveraison shoot trimming (especially severe trimming) reduced cluster weight, cluster compactness, productivity, and total yield. Effects on fruit quality included lowering of Brix and pH, with minor effects on titratable acidity, yeast assimilable nitrogen, the anthocyanin profile, and total anthocyanins. These results demonstrated that postveraison shoot trimming can be a valuable production practice by reducing cluster compactness without compromising overall fruit quality in Sangiovese.
Keywords: anthocyanin; Brix; growth; productivity; yield